Globalization, Migration, And The Evolution Of Family Values: A Philosophical Perspective - Norchaev Davron Ochilovich (Zien Journals, 2026)
In the context of accelerating globalization, international migration has become one of the most influential social phenomena shaping contemporary societies. Migration processes not only transform economic and political structures, but also deeply affect cultural norms, moral orientations, and family values. This article aims to analyze the evolution of family values under conditions of globalization and migration from a philosophical perspective. Using an interdisciplinary framework that integrates philosophy, sociology, and migration studies, the paper explores how traditional family values are reinterpreted, preserved, or transformed within migrant communities. The study follows the IMRAD structure and is based on theoretical analysis of classical and modern philosophical approaches, as well as contemporary research on migration and family transformation. The results demonstrate that migration acts as both a destabilizing and creative force, leading to the emergence of hybrid family value systems that combine traditional norms with new socio-cultural practices
Keywords: globalization; migration; family values